EFEKTIVITAS LINEN RE-USE PROGRAM PADA HOTEL DI BALI - I Gede Darmawijaya (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2017)
The objectives of this research were toidentify (1) the effectiveness of hotel’s linen re-use program and (2) the relationship between average room rate and the effectiveness of hotel’s linen re-use program in Bali. To achieve these objectives, this research made use questionnaires to collect the data from 30 hotels which were purposively sampled. The analysis method applied for this research was descriptive analysis. The results showed that the participation rate of guests to linen re-use program was 76%. The rate of efficiency achieved was 35% and the productivity rate increased at 22%. The correlation between average room rate and the effectiveness of linen re-use program was positively low with the value of “r” and “r2” was respectively 0.44 and 20%. These findings revealed that the program was very effective and the participation of guests were high irrespective their ability to pay the room. The implications of these findings were the government needs to make use the best practices of any green hotel programs by campaigning them to community to be used in government/private offices and households. The hotel could implement the green hotel program without being afraid left by their customers. The tourism and hospitality educational institution need to balance three bottom lines in teaching learning process which are people, planet and profit. Gaining profit and customer satisfaction by not sacrificing the environment, the planet.